Pelaksanaan Tindakan Supervisi Klinis Untuk Meningkatkan Kemampuan Guru SD Negeri 29 Sanggau - Jamian Jamian (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2021)
This study aims to describe clinical supervision activities as an effort to improve the ability of teachers at SD Negeri 29 Sanggau Semester 2 for the 2020/2021 academic year in preparing learning administration. The type of research is School Action Research. The research subjects were 10 teachers. Data collection techniques with document and observation techniques. Data validation using source triangulation technique and method triangulation. Data analysis technique using percentage calculation. The results showed an increase from the condition of 48.43 in the LESS criteria, and in the first cycle it became 67.78 in the ENOUGH criteria and in the second cycle of 85.56 in the GOOD criteria. An explanation of the increase in the ability to compose learning administration in the initial conditions there are no teachers who have achieved the criteria of success, and in the first cycle there are 5 teachers or 50% and in the second cycle 100% or 10 teachers are declared to have increased their ability in preparing learning administration.